(untitled) (NAU Journal of Technology and Vocational Education, 2025)
The purpose of the study is to investigate the effect of virtual laboratories on business education students’ achievement in cost accounting in public universities in Anambra State. Two research questions guided the study and two hypotheses were tested. Quasi-experimental design was adopted for the study. The population comprised 94 400-level business education students during the 2024/2025 academic session. The instrument used for data collection was a Cost Accounting Achievement Test (CAAT) developed by the researcher. The CAAT consisted of 25 multiple-choice and structured questions aligned with the university cost accounting curriculum. The instrument was validated by three experts in accounting education and measurement and evaluation. The reliability of the CAAT was determined using the Kuder-Richardson Formula 20 (KR-20), which yielded a reliability coefficient of 0.78. The experimental group was taught cost accounting using a virtual laboratory, while the control group received instruction via the conventional lecture method. Pre-test and post-test scores were analyzed using descriptive statistics and Analysis of Covariance (ANCOVA) at 0.05 level of significance. The findings revealed that students taught with the virtual laboratory significantly outperformed those taught using the conventional lecture method. Female students achieved higher mean scores than male students, although the interaction effect of method and gender was not significant, indicating that the virtual laboratory enhanced achievement of male and female students. The study concluded that virtual laboratory significantly enhanced students’ achievement in cost accounting in public universities in Anambra State. It was therefore recommended among others that accounting educators should integrate virtual laboratories into cost accounting courses to enhance students’ academic achievement.